Graphene oxide as high-performance dielectric materials for capacitive pressure sensors. (April 2017) - Wan, Shu; Bi, Hengchang; Zhou, Yilong; Xie, Xiao; Su, Shi; Yin, Kuibo; Sun, Litao
Abstract: Graphene oxide (GO) foam exhibits both excellent elastic property and high relative dielectric permittivity, which is a novel building block for future wearable electronic devices. Herein we present an ultra-sensitive GO-based capacitive pressure sensor with graphene as electrodes by an efficient, low-cost fabrication strategy over large-area integration as well as patterning for recording spatial pressure distribution. The GO-based sensor can detect a subtle pressure of ∼0.24Pa with a fast response time (∼100 m) and a high sensitivity (∼0.8 kPa −1 ). The superior sensing properties combining with good flexibility and robustness reveal a great application potential in various fields, such as health monitoring, flexible human-computer user interfaces, and robotics, which also give a new insight for all-carbon electronics. Graphical abstract: